2016
DOI: 10.1186/s40104-016-0078-8
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids and mammary gland development: nutritional implications for milk production and neonatal growth

Abstract: Milk is synthesized by mammary epithelial cells of lactating mammals. The synthetic capacity of the mammary gland depends largely on the number and efficiency of functional mammary epithelial cells. Structural development of the mammary gland occurs during fetal growth, prepubertal and post-pubertal periods, pregnancy, and lactation under the control of various hormones (particularly estrogen, growth hormone, insulin-like growth factor-I, progesterone, placental lactogen, and prolactin) in a species-and stage-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
131
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(137 citation statements)
references
References 137 publications
4
131
1
1
Order By: Relevance
“…The number of mammary cells and the amount of nutrients available to those mammary cells are the main determinants of milk production (Kim and Wu 2009). Hence, promoting the proliferation of mammary epithelial cells and enhancing their synthesis of milk-specific proteins are two effective ways to improve the lactation performance of mammals (Bauman et al 2008;Rezaei et al 2016). In recent years, studies have focused on nutritional and hormonal regulation of mammary gland metabolism (McCormick et al 2014;Wang et al 2014;Lei et al 2012aLei et al , b, 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of mammary cells and the amount of nutrients available to those mammary cells are the main determinants of milk production (Kim and Wu 2009). Hence, promoting the proliferation of mammary epithelial cells and enhancing their synthesis of milk-specific proteins are two effective ways to improve the lactation performance of mammals (Bauman et al 2008;Rezaei et al 2016). In recent years, studies have focused on nutritional and hormonal regulation of mammary gland metabolism (McCormick et al 2014;Wang et al 2014;Lei et al 2012aLei et al , b, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The lactation performance of sows plays a key role in pork production (Rezaei et al 2016). It has been suggested that the milk yield of sows is influenced by various factors such as genotype, nutrition (Quesnel et al 2009), physical activity and sucking stimulation (Malmkvist et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Polyamines are synthesised by lactating mammary tissue [6] and are involved in the hormonal regulation of lactogenic processes in the mammary gland [7] , which can explain their presence in milk. A large individual variation in polyamine levels in human milk has been recorded and is related to the age of the mother, ethnic origin, dietary intake of polyamines and nutritional status, among other factors [3,8] .…”
mentioning
confidence: 99%
“…Ensuring adequate mammary epithelial cells helps improve milk production by bovines. The proliferation of mammary gland cells is controlled by numerous elements, such as hormones and nutrients (Osorio, Lohakare, & Bionaz, ; Rezaei, Wu, Hou, Bazer, & Wu, ). It has been reported that estrogens recognize the estrogen receptor and then promote the proliferation of mammary epithelial cells during puberty (Brisken & O'Malley, ).…”
Section: Introductionmentioning
confidence: 99%